Dual Training at a Glance - (:unkn) unknown (My University, 2011)
Die vorliegende Schaubildsammlung gibt einen Überblick über das Berufsbildungssystem und skizziert die Wesensmerkmale der dualen Ausbildung in Deutschland. (BIBB-Doku) Inhalt: 1. Federal Ministry of Education and Research (BMBF) 2. Dual Training 3. From school to work 4. Training occupations in the dual system 5. Arguments in favour of dual training 6. Division of responsibilities in dual training 7. Facts and figures 8. The history of vocational training.
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; Berufsbildungssystem; Duales System; Berufseinmündung; Lernort Betrieb; Lernort Schule; Berufsausbildung; Attraktivität; Historische Entwicklung